2020
DOI: 10.1371/journal.pone.0235084
|View full text |Cite
|
Sign up to set email alerts
|

Addition of terlipressin to initial volume resuscitation in a pediatric model of hemorrhagic shock improves hemodynamics and cerebral perfusion

Abstract: Hemorrhagic shock is one of the leading causes of mortality and morbidity in pediatric trauma. Current treatment based on volume resuscitation is associated to adverse effects, and it has been proposed that vasopressors may be used in the pharmacological management of trauma. Terlipressin has demonstrated its usefulness in other pediatric critical care scenarios and its long half-life allows its use as a bolus in an outpatient critical settings. The aim of this study was to analyze whether the addition of a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…The goal of initial trauma resuscitation should be to rescue the cardiopulmonary system but while doing so, preserve and protect the central nervous system. Cerebral perfusion is an important resuscitation endpoint to assess the neurological status of survivors ( van den Brule et al, 2018 ; Lorusso and Bělohlávek, 2020 ; Gil-Anton et al, 2020 ). Computed tomography perfusion (CTP) scanning offers a non-invasive method to assess for cerebral perfusion ( Abdou et al, 2021 ; Abdou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of initial trauma resuscitation should be to rescue the cardiopulmonary system but while doing so, preserve and protect the central nervous system. Cerebral perfusion is an important resuscitation endpoint to assess the neurological status of survivors ( van den Brule et al, 2018 ; Lorusso and Bělohlávek, 2020 ; Gil-Anton et al, 2020 ). Computed tomography perfusion (CTP) scanning offers a non-invasive method to assess for cerebral perfusion ( Abdou et al, 2021 ; Abdou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Terlipressin has been studied as a vasoactive drug for the management of catecholamine-resistant arterial hypotension in septic shock 46 , liver failure 25 , and acute gastrointestinal bleeding 26 . The effects of terlipressin consist of vasoconstrictor activity in vascular smooth muscle cells and pronounced vasoconstriction within the splanchnic circulation, having been shown to redistribute blood flow in order to restore perfusion pressure to organs such as the liver, kidneys, and brain 27 , as well as to increase survival rates in animal models of HS 47 . In the HS model employed in the present study, we found that treatment with terlipressin and conservative fluid management increased post-HS survival.…”
Section: Discussionmentioning
confidence: 99%
“…Terlipressin has been studied as a vasoactive drug for the management of catecholamineresistant arterial hypotension in septic shock [46], liver failure [25], and acute gastrointestinal bleeding [26]. The effects of terlipressin consist of vasoconstrictor activity in vascular smooth muscle cells and pronounced vasoconstriction within the splanchnic circulation, having been shown to redistribute blood ow in order to restore perfusion pressure to organs such as the liver, kidneys, and brain [27], as well as to increase survival rates in animal models of HS [47]. In the HS model employed in the present study, we found that treatment with terlipressin increased post-HS survival.…”
Section: Discussionmentioning
confidence: 99%